The Use of Internet Reporting for Small Business - Heenetigala , Kumudini; Armstrong , Anona (Journal of Law and Governance, 2009)
Small business is receiving increasing attention from government because of its potential to drive innovation and economic growth in the wake of the global financial crisis. The lean governance structures in small business mean that decisions are quickly made and implemented. Multiple decisions can modify production processes, produce a new product, apply new marketing methods or tap new markets. These decisions are deeply connected with issues of technological capability and incentives to invest in new innovations. However, many small businesses are likely to have limited access to skills, and lack information about markets and technology. Knowledge about these issues in small businesses is often provided by their accountants. The purpose of this study was to determine how accountants could assist small businesses to make better use of emerging web based technologies to communicate with their accountants. The research was supported by a major grant from the National Institute of Accountants. This paper reports research in which twenty two accountants and their clients were interviewed to determine the potential adoption and use of web based information and communications technology to provide immediate on-going communication between small businesses and their accountants. It is the first article to investigate the support for and barriers to the use of interactive technology to promote small business via the web. The research questions addressed in this paper were: What uses do small businesses currently made of ICT? What are some of the new opportunities offered by ICT to accountants? What are the barriers to the use of new technology? What are the benefits to accountants and their small business clients?